2021
DOI: 10.1111/petr.14138
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in monitoring pediatric LT patients before and during COVID‐19 pandemic

Abstract: Background The delivery of healthcare services by telemedicine decreases costs of traveling for patients, is less time‐consuming, and most importantly permits the connection between highly skilled specialists and patients. However, whether the use of telemedicine (text messaging) for LT patients was affected by the COVID‐19 pandemic is unknown. Methods We collected data (following consent from patients and parents) from 57 patients (33 male/24 female) with a median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…A detailed explanation of the inclusion/exclusion process can be found in Figure 17 (PRISMA fig). A total of 12 studies [50][51][52][53][54][55][56][57][58][59][60][61] were conducted in the adult population, and 1 study focused on children 62 with a total of 2216 telehealth consultations. As there were a limited number of studies with consistent outcomes measures of telehealth, pooled analysis could not be performed.…”
Section: Telehealth In Solid Organ Transplant Recipient Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed explanation of the inclusion/exclusion process can be found in Figure 17 (PRISMA fig). A total of 12 studies [50][51][52][53][54][55][56][57][58][59][60][61] were conducted in the adult population, and 1 study focused on children 62 with a total of 2216 telehealth consultations. As there were a limited number of studies with consistent outcomes measures of telehealth, pooled analysis could not be performed.…”
Section: Telehealth In Solid Organ Transplant Recipient Resultsmentioning
confidence: 99%
“…As there were a limited number of studies with consistent outcomes measures of telehealth, pooled analysis could not be performed. Overall, there were 4/13 studies that reported high medical adherence rate (>70%), [50][51][52]61 6/13 studies reported excellent or high satisfaction rates from both patients and physicians, [53][54][55][56]60,62 and 2/13 studies highlighted the ability to obtain accurate BP, weight, and other measurements (77.45%). 57,63 With most consultation appointments able to be conducted virtually, only a handful of patients needed in-person followup visitations, specifically 33/197 patients (two studies).…”
Section: Telehealth In Solid Organ Transplant Recipient Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The year 2020 was seriously impacted by the global spread of COVID-19, which necessitated the promotion of new health care initiatives and a reorganization of telemedicine to meet patients' expectations for broader access [10][11][12][13][14]. The unstructured and opportunistic implementations of many telemedicine devices and protocols during the pandemic have cast light on the urgent need for standardization [15,16].…”
Section: Introductionmentioning
confidence: 99%